Pengaruh Struktur Modal, Net Profit Margin (NPM) dan Ukuran Perusahaan terhadap Kebijakan Dividen pada Perusahaan Sub Sektor Consumer Goods yang terdaftar di Bursa Efek Indonesia Periode 2011-2015 - Lubis, Mahmuddin Syah; -, Yusneni Afrita Nasution; -, Elim Suryenti (Jurnal Ekonomi Bisnis Manajemen Prima, 2020)
The objective of the research was to examine and analyze the influence of capital structure, net profit margin and company size on dividend policy in consumer goods sub-sector companies listed in the Indonesia Stock Exchange period 2011-2015. The research used descriptive research methode. The population was 40 companies in the consumer goods sub-sector listed in the Indonesia Stock Exchange for the period 2011 – 2015, and 17 of them were used as the samples, taken by using purposive sampling technique. The data were analyzed by using multiple linear regression using SPSS. The results of the research showed that the variables of Capital Structure, Net Profit Margin and Company Size simultaneously had influence on Dividend Policy. Partially, Capital Structure had insignificant influence on Dividend Policy, Net Profit Margin had positive and significant influence on Dividend Policy and Company Size had positive and significant influence on Dividend Policy.